Chemical properties and microbiological quality of three hazelnut varieties cultivated in Portugal - Ferrão, A. C. (2022)
Hazelnut is a dried fruit that stands out for its organoleptic and nutritional characteristics and therefore is highly appreciated globally. Worldwide, there are several hazelnut varieties, and their characteristics are dependent on the genotype, agricultural techniques, post-harvest practices, geographic location and climatic conditions. In addition, the physicochemical characteristics influence the quality and shelf life of this fruit [1]. Therefore, the aim of this study was to analyse some chemical properties and also the microbiological quality of three hazelnut varieties (Grada de Viseu, Tonda de Giffoni and Butler) cultivated in Portugal. For that purpose, hazelnut kernels were analysed for moisture, water activity, fat, protein, ash and the specific extinction coefficients (K232, K268 and ΔK which is calculated from the values of the specific extinction coefficients at 264 and 272 nm). It was also performed a quantification of microorganisms at 30⁰C and of moulds and yeasts at 25⁰C. The results showed that fat was the major component for all the varieties, ranging from 70.14±1.75 g/100 g (var. Butler) to 66.46±5.33 g/100 g (var. Tonda), with no significant differences between the varieties. All analyses were done in triplicate. The fruits of the variety Grada had a higher moisture content (6.01±0.26 g/100 g), while the fruits of the var. Tonda (4.78±0.40 g/100 g) presented the lowest value, but in this case with statistically significant differences (p=0.004). According to the recommendations of the European Union, moisture content of hazelnut kernels should not exceed 6.0% [2] Regarding the water activity, the lowest value was observed for the var. Tonda (0.54±0.01), followed by the var. Butler (0.55±0.01) and finally the var. Grada (0.56±0.01), with no significant differences between them. The var. Grada was the one with the highest ash (2.73±0.08 g/100 g), fibre (6.35±0.25 g/100 g) and protein content (18.00±0.34 g/100 g), with statistically significant differences between the varieties in the three cases. Specific extinction coefficients are related to oxidation processes and provide information about the quality of the oil extracted from hazelnuts, as well as its state of conservation. The fruits from the var. Grada presented the lowest value of K232 (0.54±0.01), followed by the var. Butler (0.59±0.01) and in last the var. Tonda (0.80±0.08), which means that the fruits of the var. Tonda had more primary oxidation products, being the results for this var. statistically different from the others. As for the K268, all the varieties presented values close to zero (Var. Grada=0.03±0.00, var. Tonda=0.04±0.00 and var. Butler=0.03±0.00), meaning that all the samples had low levels of secondary oxidation compounds. Furthermore, there were no significant differences between the varieties (p=0.373). The values of the ΔK ranged from 0.004±0.00 for the varieties Grada and Butler and 0.003±0.00 for the var. Tonda, again with no statistically significant differences, which means that it is a fresh and well-preserved oil. Regarding the microbiological results, as it can be observed in Table 1, all the varieties presented a satisfactory microbiological quality in accordance with the limits established for the count of microorganisms at 30⁰C and mould and yeast by the National Health Institute Doutor Ricardo Jorge [3] (<106 CFU/g for microorganisms at 30⁰C, <105 CFU/g for yeast and <5x102 CFU/g for moulds). Moreover, there were found statistically significant differences among the varieties under study. It is important to highlight that var. Grada was that one that presented more microorganisms at 30⁰C and also more moulds and yeast, when compared to the other varieties. This may be due to the higher moisture content of this variety.The results of this study provided important information about the chemical properties and microbiological quality of the most representative hazelnut varieties cultivated in Portugal.